2013
DOI: 10.1007/s00059-013-3788-0
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride-to-HDL cholesterol ratio

Abstract: The TG/HDL-C ratio is predictive of the severity of CHD. It could also help predict in-hospital new-onset heart failure incidents of CHD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…Our findings are consistent with the results of a hospital-based study [ 9 ], in which Yang D et al demonstrated that the TG/HDL-C ratio was not associated with the Gensini scores in Chinese CHD patients. However, in another case–control study which was also involved in Chinese CHD patients, Yunke Z et al [ 11 ] reported that the TG/HDL-C ratio can predict the severity of CHD and the incident of new-onset heart failure among in-hospital CHD patients. In Brazilians, da Luz PL et al [ 12 ] also demonstrated that the TG/HDL-C ratio was associated with the severity of CHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with the results of a hospital-based study [ 9 ], in which Yang D et al demonstrated that the TG/HDL-C ratio was not associated with the Gensini scores in Chinese CHD patients. However, in another case–control study which was also involved in Chinese CHD patients, Yunke Z et al [ 11 ] reported that the TG/HDL-C ratio can predict the severity of CHD and the incident of new-onset heart failure among in-hospital CHD patients. In Brazilians, da Luz PL et al [ 12 ] also demonstrated that the TG/HDL-C ratio was associated with the severity of CHD.…”
Section: Discussionmentioning
confidence: 99%
“…A recent cross-sectional association study [ 10 ] in a Lebanese population further revealed that the TC/HDL-C ratio ≥4 significantly predicts ≥50 % stenosis in all vessels. The ratio of TG/HDL-C was also found to be associated with the severity of CHD in two studies from Ruijin Hospital, Shanghai Jiaotong University, China [ 11 ] and Insituto do Coração, Universidade de São Paulo, Brazil [ 12 ], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The triglyceride to high-density lipoprotein cholesterol (TG/HDL-C) ratio has been widely used as a reliable marker of insulin resistance 8 and has a positive correlation with the incidence of type 2 diabetes and metabolic syndrome. 9 Meanwhile, TG/HDL ratio has also been demonstrated to be correlated with cardiovascular diseases, including hypertension, 10 coronary heart disease (CHD), 11 new-onset heart failure, 12 and myocardial infarction. 13 …”
Section: Introductionmentioning
confidence: 99%
“…47–51 The −5.85% (−10.5% to −1.15%; P = .0161) and −7.44% (−13.7% to −1.18%; P = .0211) decreases, respectively, in TC/HDL and TG/HDL reflected improved glycemic control by NFC in DM and DM/OW individuals, as well as decreased cardiovascular disease risk and heart failure risk. 50 , 52 , 53 In this study TC/HDL and TG/HDL were positively correlated with improvements in markers of insulin resistance such as LAP ( r = 0.478; and r = 0.669, respective; P < .0001 for both), FLI ( r = 0.320, P = .0038; r = 0.304, P = .0061, respectively), and number of MetS defining criteria ( r = 0.271, P = .0149; r = 0.262, P = .0190), while only TC/HDL was positively correlated with improvements in BMI ( r = 0.232, P = .038).…”
Section: Discussionmentioning
confidence: 99%